An In Silico Evaluation of the Anti-Wrinkling Potential of Certain Peptides in Relation to the Catalytic Domain of Matrix Metalloproteinase-1 - Rahmadani, Agung; Sukemi, Sukemi; Tasya, Indriana; Olii, Nova Yunita Putri; Ridwansyah, Muhammad; Turista, Dora Dayu Rahma; Arifian, Hanggara (Jurnal Sains dan Kesehatan, 2025)
Skin wrinkles are caused by the cleavage of collagen fibers by the major collagenase enzyme matrix metalloproteinase-1 (MMP-1). Peptide-based matrix metalloproteinase-1 inhibitors present a potential new therapeutic strategy to prevent MMP-1-mediated collagenolysis, which is induced by UV-induced MMP-1 overexpression. This in silico study investigated the MMP-1 inhibitory capacity of carefully selected and well-designed hexapeptides. A molecular docking method was employed to screen 14 hexapeptides. The target ligands were observed to interact non-covalently. The LYYYGP peptide sequence was found to form three hydrogen bonds (H-bonds) with amino acid (AA) residues in the catalytic domain of MMP-1. Additionally, hydrophobic interactions between these peptides and the protein were observed at certain sites. The maximum binding affinity was observed for the LYYYGP sequence (binding free energy, ?G = -9.00 kcal/mol). These sequences exhibited binding energies comparable to those of the LSYYGP sequence (-8.48 kcal/mol) and YSGYYP sequence (-8.27 kcal/mol). The YSGYGY sequence demonstrated a lower binding affinity for the target receptor, with ?G = -5.59 kcal/mol. This study indicates that specific peptide sequence components are crucial for forming hydrogen bonds that link proteins to peptides. Further investigation, encompassing chemical synthesis and laboratory experimentation, is requisite to substantiate the efficacy of the two hexapeptides.